Antiherpetic Medication Use and the Risk of Gastroschisis: Findings from the National Birth Defects Prevention Study, 1997–2007. Issue 4 (3rd June 2013) - Ahrens, Katherine A.; Anderka, Marlene T.; Feldkamp, Marcia L.; Canfield, Mark A.; Mitchell, Allen A.; Werler, Martha M.
Abstract: Background: Previous studies examining the teratogenic effects of antiherpetic medications have found no associations for birth defects overall but have not examined the risk of specific birth defects. Methods: The National Birth Defects Prevention Study ascertains population‐based cases with birth defects and live‐born controls without birth defects in 10 states across the United States for the purpose of identifying potential teratogenic risk factors. Mothers of cases and controls are interviewed within 2 years of their estimated date of delivery about demographic, medical and behavioural factors before and during pregnancy. This analysis examined the possible association between use of antiherpetic medications (acyclovir, valacyclovir or famciclovir) during early pregnancy and gastroschisis, a birth defect of the abdominal wall. Results: The mothers of 1.1% ( n = 10) of 941 gastroschisis cases and 0.3% ( n = 27) of 8339 controls reported antiherpetic medication use during the month before conception through the third month of pregnancy. The adjusted odds ratios for such use in relation to gastroschisis were 4.7 [95% confidence interval 1.7, 13.3] and 4.7 [95% CI 1.2, 19.0] among women with and without self‐reported genital herpes, respectively, when compared with women without antiherpetic use or herpes. Among women reporting no antiherpetic medication use, the odds ratio for self‐reported genital herpes in relation to gastroschisis was 3.0 [95% CI 1.6, 5.7]. Conclusions: Our study raises the possibility of an increased risk of gastroschisis because of either antiherpetic medication use during early pregnancy or the underlying genital herpes infection for which it was indicated.